2018
DOI: 10.1016/j.celrep.2018.11.024
|View full text |Cite
|
Sign up to set email alerts
|

The HDAC-Associated Sin3B Protein Represses DREAM Complex Targets and Cooperates with APC/C to Promote Quiescence

Abstract: SUMMARY The mammalian DREAM complex is responsible for the transcriptional repression of hundreds of cell-cycle-related genes in quiescence. How the DREAM complex recruits chromatin-modifying entities to aid in its repression remains unknown. Using unbiased proteomics analysis, we have uncovered a robust association between the chromatin-associated Sin3B protein and the DREAM complex. We have determined that genetic inactivation of Sin3B results in the de-repression of DREAM target genes during quiescence but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 61 publications
8
41
1
Order By: Relevance
“…histone tails and core, MuvB could prevent the unwrapping and movement of the +1 nucleosome. Although initial mass spectrometry analysis revealed few binding partners to human MuvB that could explain its repressive role, more recent studies have found MuvB can in certain contexts recruit proteins such as Sin3A (Bainor et al, 2018;Kim et al, 2021). Additional factors may also function to enhance repression in addition to the nucleosome binding activity of MuvB.…”
Section: Discussionmentioning
confidence: 99%
“…histone tails and core, MuvB could prevent the unwrapping and movement of the +1 nucleosome. Although initial mass spectrometry analysis revealed few binding partners to human MuvB that could explain its repressive role, more recent studies have found MuvB can in certain contexts recruit proteins such as Sin3A (Bainor et al, 2018;Kim et al, 2021). Additional factors may also function to enhance repression in addition to the nucleosome binding activity of MuvB.…”
Section: Discussionmentioning
confidence: 99%
“…The control of quiescence entry by cell cycle-independent integrators of stress stimuli could provide an adaptive advantage in environments with strong fluctuations of nutrients, as is the case for parasites with complex life cycles and cancer cells attempting metastasis (Wang et al, 2015). In mammalian cells, transcriptional repressors that could play an analogous role to Xbp1 are HES1 (Sueda et al, 2019, Coller, 2011 and the DREAM complex (Bainor et al, 2018, Miles and Breeden, 2017, Schade et al, 2019; however, it is unknown whether they can act as integrators of stress stimuli during quiescence entry. At least in prophase I mouse oocytes, it is clear that transcriptional repression by histone deacetylase-regulators akin to Xbp1 is essential to maintain a high-Cdk1 quiescent state (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…synthesis or enter mitosis. As a complementary approach, we expressed and imaged the FUCCI sensor mKO2-Cdt1 (30-120) (Bainor et al, 2018;Sakaue-Sawano et al, 2008) and EGFP-PCNA in cells that had been synchronized by serum starvation and refed in the presence of 1-NM-PP1. The midpoint of Cdt1 degradation was used to identify the G1/S boundary, while PCNA foci were used to monitor DNA replication.…”
Section: Human Cells Exhibit Escalating Sensitivity To Ddki Across S mentioning
confidence: 99%